1988
DOI: 10.1111/j.1432-1033.1988.tb14248.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal and cytosolic epoxide hydrolases, the peroxisomal fatty acid β‐oxidation system and catalase

Abstract: A number of structurally unrelated hypolipidaemic agents and certain phthalate-ester plasticizers induce hepatomegaly and proliferation of peroxisomes in rodent liver, but there is relatively limited data regarding the specific effects of these drugs on liver non-parenchymal cells. In the present study, liver parenchymal, Kupffer and endothelial cells from untreated and fenofibrate-fed rats were isolated and the activities of two enzymes associated with peroxisomes (catalase and the peroxisomal fatty acid P-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…This is consistent with observations in many other cell types and in humans in vivo [18]. Synthesis of DHA from DPA requires peroxosomal -oxidation and there is a report that ECs from rats do not express peroxisomal fatty acid -oxidation activity [45]. Future work should address this pathway in more detail in human ECs.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with observations in many other cell types and in humans in vivo [18]. Synthesis of DHA from DPA requires peroxosomal -oxidation and there is a report that ECs from rats do not express peroxisomal fatty acid -oxidation activity [45]. Future work should address this pathway in more detail in human ECs.…”
Section: Discussionsupporting
confidence: 89%
“…Metabolic activities of enzymes involved in the detoxification pathways of VC-reactive metabolites, such as epoxide hydrolase and glutathione S-transferases, are localized mainly in parenchymal rather than non-parenchymal liver cells [19,20]. Indeed, notwithstanding the presumably much higher amounts of CEO in hepatocytes, where it is formed, than in non-parenchymal cells, similar N 2 ,3-ethenoguanine concentrations have been observed in these different liver cell types [9], consistent with preferential metabolic inactivation of CEO in hepatocytes.…”
Section: Liver Cell Targets Of Vc-induced Carcinogenesismentioning
confidence: 99%
“…They constitute about 30 % of all liver cells, but they occupy only about 6 of total liver volume (Fabrikant, 1968;Greengard et al, 1972 Blouin et al, 1977;Blomhoff et al, 1984). In previous studies (Steinberg et al, 1987(Steinberg et al, , 1988 it was shown that oxidative and post-oxidative drug-metabolizing enzymes are not restricted to parenchymal cells in rat liver: in Kupffer and endothelial cells the activities of oxidative enzymes (e.g. aminopyrine N-demethylase, ethoxyresorufin O-de-ethylase) are very low, whereas the postoxidative enzyme activities (glutathione S-transferase, epoxide hydrolase) are relatively high.…”
Section: Introductionmentioning
confidence: 94%